HUBUNGAN ANTARA KEMAMPUAN KOMUNIKASI MATEMATIS, KEMANDIRIAN BELAJAR, DAN SELF-EFFICACY PESERTA DIDIK KELAS VIII DALAM PEMBELAJARAN MATEMATIKA - Nenna Nur Islami, - (2022)
Mathematics communication ability is one of the important abilities that students must have. Beside that, students must also have affective abilities, there are self regulated learning and self efficacy. This study aimed to determine: (1) is there a significant correlation between mathematical communication ability and self regulated learning; (2) is there a significant correlation between mathematical communication ability and self efficacy; and (3) is there a significant correlation between self regulated learning and self efficacy. This study used a quantitative approach with correlational design. The population in this study were all eighth grade students in Junior High School in Garut, West Java Province. The sample were 61 students from three different classes. Based on the result of the study, it was found that; (1) there was no significant correlation between mathematical communication ability and self regulated learning; (2) there was a significant relationship between mathematical communication skills and self efficacy; and (3) there was a significant relationship between self regulated learning and self efficacy.